Integrated Islamic Education Curriculum According to Tuan Guru Sekumpul Syekh Muhammad Zaini - Muhammad Yusran; Mahyuddin Barni; Noor Azmah Hidayati (At-Taqaddum, 2025)
The curriculum is very important in education because it has a direct impact on students. In its definition, the curriculum is divided into three parts: subjects, learning experiences, and planning. There are visible and invisible curricula. The invisible curriculum is the educational environment or the ideas of scholars. These ideas arise as an effort to contextualise Islamic teachings in the face of various changes. The Islamic religious education curriculum in terms of material is fixed and stagnant. However, there are differences among scholars regarding the order in which the material should be taught to students. This paper will attempt to describe the curriculum ideas of Tuan Guru Sekumpul Syekh Muhammad Zaini, also known as Guru Sekumpul. The researcher is interested in studying this figure because of his prominence, breadth of knowledge, and influence on the people of Kalimantan, especially South Kalimantan. The main references are sourced from lecture CDs/MP3s delivered by Tuan Guru Zaini during his lifetime and compared with the books he read. Using a qualitative approach and content analysis, Tuan Guru Zaini's ideas about the PAI curriculum were discovered. With a qualitative approach and content analysis, it was found that Tuan Guru Zaini's ideas on PAI (Islamic Education) curriculum emphasize moral education, spirituality, and the integration of Sharia and Sufism, as well as implications for the development of an Islamic education curriculum that is more contextual and spiritually oriented